An Analysis of TikTok Engagement Optimization Strategies: A Case Study of the Bakpia Juwara Satoe Account - Wahyu Purnomo; Guntur Andi Pamungkas; Cita Amalia (International Journal of Economic and Tourism Research, 2026)
The rapid growth of TikTok as an algorithm-driven social media platform has encouraged small and medium-sized enterprises (SMEs) to adopt innovative digital marketing strategies to enhance audience engagement. This study aims to analyze the engagement strategy implemented by Bakpia Juwara Satoe, a local culinary brand that utilizes TikTok as a primary communication and promotional medium. Employing a qualitative research design with a descriptive case study approach, this research explores how content planning, visual presentation, interaction management, and credibility-building practices contribute to audience engagement. Data were collected through in-depth interviews with account managers, participant observation of audience interactions, and analysis of internal TikTok analytics and content archives. The findings reveal that Bakpia Juwara Satoe applies an adaptive–predictive content planning strategy, supported by strong visual identity, the use of attention-grabbing hooks, and active two-way communication in the comment section. Additionally, authentic storytelling and transparent product information play a crucial role in strengthening audience trust and sustaining engagement. The study concludes that effective TikTok engagement for SMEs is not solely dependent on video-centric content, but rather on strategic relevance, visual consistency, and relational communication. These findings contribute to the literature on social media marketing by demonstrating the potential of alternative content formats and engagement-oriented strategies for culinary SMEs operating in competitive digital environments.